Permissive hypercapnia in extremely low birthweight infants (PHELBI): a randomised controlled multicentre trial. Issue 7 (July 2015) - Thome, Ulrich H; Genzel-Boroviczeny, Orsolya; Bohnhorst, Bettina; Schmid, Manuel; Fuchs, Hans; Rohde, Oliver; Avenarius, Stefan; Topf, Hans-Georg; Zimmermann, Andrea; Faas, Dirk; Timme, Katharina; Kleinlein, Barbara; et al.
Summary Background Tolerating higher partial pressure of carbon dioxide (pCO2) in mechanically ventilated, extremely low birthweight infants might reduce ventilator-induced lung injury and bronchopulmonary dysplasia. We aimed to test the hypothesis that higher target ranges for pCO2 decrease the rate of bronchopulmonary dysplasia or death. Methods In this randomised multicentre trial, we recruited infants from 16 tertiary care perinatal centres in Germany with birthweight between 400 g and 1000 g and gestational age 23–28 weeks plus 6 days, who needed endotracheal intubation and mechanical ventilation within 24 h of birth. Infants were randomly assigned to either a high target or control group. The high target group aimed at pCO2 values of 55–65 mm Hg on postnatal days 1–3, 60–70 mm Hg on days 4–6, and 65–75 mm Hg on days 7–14, and the control target at pCO2 40–50 mmHg on days 1–3, 45–55 mm Hg on days 4–6, and 50–60 mm Hg on days 7–14. The primary outcome was death or moderate to severe bronchopulmonary dysplasia, defined as need for mechanical pressure support or supplemental oxygen at 36 weeks postmenstrual age. Cranial ultrasonograms were assessed centrally by a masked paediatric radiologist. This trial is registered with the ISRCTN registry, number ISRCTN56143743. Results Between March 1, 2008, and July 31, 2012, we recruited 362 patients of whom three dropped out, leaving 179 patients in the high target and 180 in the control group. The trial was stopped after an interim analysis (n=359). The rate of bronchopulmonary dysplasia or death in the high target group (65/179 [36%]) did not differ significantly from the control group (54/180 [30%]; p=0·18). Mortality was 25 (14%) in the high target group and 19 (11%; p=0·32) in the control group, grade 3–4 intraventricular haemorrhage was 26 (15%) and 21 (12%; p=0·30), and the rate of severe retinopathy recorded was 20 (11%) and 26 (14%; p=0·36). Interpretation Targeting a higher pCO2 did not decrease the rate of bronchopulmonary dysplasia or death in ventilated preterm infants. The rates of mortality, intraventricular haemorrhage, and retinopathy did not differ between groups. These results suggest that higher pCO2 targets than in the slightly hypercapnic control group do not confer increased benefits such as lung protection. Funding Deutsche Forschungsgemeinschaft.